2013
DOI: 10.1002/ccd.25261
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obstructive coronary artery disease in patients undergoing lung transplantation: Case series and review of the literature

Abstract: Background Coronary angiography is commonly performed prior to lung transplantation, but its utility is unproven. Methods We conducted a single-center retrospective analysis of consecutive patients referred for coronary angiography as part of a pre-operative evaluation for lung transplantation and reviewed the literature for prior series. Results A total of 89 patients, 48 men and 41 women were included. Obstructive (≥ 70% stenosis) CAD was present in 9 (10%), non-obstructive (< 70% stenosis) CAD in 24 (27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…As there is a high incidence of CAD in the lung transplant population, the arguments for and against routine preoperative CA have been debated by other investigators . Stenting lesions in asymptomatic lesions are in general discouraged by the American College of Cardiology Foundation in its appropriate use criteria document .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As there is a high incidence of CAD in the lung transplant population, the arguments for and against routine preoperative CA have been debated by other investigators . Stenting lesions in asymptomatic lesions are in general discouraged by the American College of Cardiology Foundation in its appropriate use criteria document .…”
Section: Discussionmentioning
confidence: 99%
“…For coronary artery disease, end‐organ ischemia has immediate consequences that can progress to infarction, heart failure, or arrhythmia. For this reason, LT patients at risk of coronary artery disease (CAD) routinely undergo preoperative coronary angiography (CA) . Depending on the definition used, CAD is present in 10%‐60% of patients with advanced lung disease .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They determined a prevalence of obstructive CAD of 10% in lung transplant patients at their center. 15 They also searched for published research and included 13 articles that matched their criteria. Of those 13 studies, only five defined CAD the same as they did.…”
Section: Prevalence Of Coronary Artery Disease In Lung Transplant Pmentioning
confidence: 99%
“…When analyzing the results from the six studies, the conclusion was that prevalence of obstructive CAD in lung transplant patients was 11%. [15][16][17][18][19][20] reported that in patients with >4 risk factors CAD was always significant. However, they stated that patients with <3 risk factors still had 11% risk of significant CAD.…”
Section: Prevalence Of Coronary Artery Disease In Lung Transplant Pmentioning
confidence: 99%